2017
DOI: 10.1016/j.actamat.2016.12.046
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of radiation-induced segregation in CrFeCoNi-based single-phase concentrated solid solution alloys

Abstract: Single-phase concentrated solid solution alloys have attracted wide interest due to their superior mechanical properties and enhanced radiation tolerance, which make them promising candidates for the structural applications in next-generation nuclear reactors. However, little has been understood about the intrinsic stability of their as-synthesized high-entropy configurations against radiation damage. Here we report the element segregation in CrFeCoNi, CrFeCoNiMn, and CrFeCoNiPd equiatomic alloys when subjecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 148 publications
(60 citation statements)
references
References 53 publications
4
55
1
Order By: Relevance
“…Furthermore, a trend of reducing RIS level has been observed with increasing compositional complexity, from NiFe, NiCoFe, NiCoFeCr, to NiCoFeCrMn . For all the observed RIS cases, as representatively shown in Figures 7c,d, Ni and Co tend to enrich, but Cr, Fe, and Mn prefer to deplete near the defects (grain boundaries, loops, and voids) (He et al, 2017;Lu et al, 2017;Yang et al, 2018).…”
Section: Response To the Irradiations At Elevated Temperaturesmentioning
confidence: 93%
See 1 more Smart Citation
“…Furthermore, a trend of reducing RIS level has been observed with increasing compositional complexity, from NiFe, NiCoFe, NiCoFeCr, to NiCoFeCrMn . For all the observed RIS cases, as representatively shown in Figures 7c,d, Ni and Co tend to enrich, but Cr, Fe, and Mn prefer to deplete near the defects (grain boundaries, loops, and voids) (He et al, 2017;Lu et al, 2017;Yang et al, 2018).…”
Section: Response To the Irradiations At Elevated Temperaturesmentioning
confidence: 93%
“…No secondary phases have been observed in any of the above materials under ion irradiations (including NiFe,NiCoFe,NiCoFeCr,NiCoFeCrMn,FeNiMnCr 0.66 , and NiCoFeCrAl 0.1 ) at all conditions, suggesting a great phase stability. However, the electron-irradiated NiCoFeCrMn and NiCoFeCrPd thin foils (TEM samples) have shown L10 (NiMn)-type ordering decomposition and <001>-oriented spinodal decomposition between Co/Ni and Pd, respectively, even at a low dose of 1 dpa (He et al, 2017). While not being single-phase by itself, the FCC solid-solution phase portion in NiCoFeCrCu nanocrystalline sample also maintains high phase stability against electron irradiation at temperatures up to 500 • C (Nagase et al, 2015).…”
Section: Response To the Irradiations At Elevated Temperaturesmentioning
confidence: 99%
“…It was found that the CoCrFeNiMn HEA did not change significantly after 773 K high-temperature and 3 MeV Ni ions irradiation, and the grains did not coarsen. High performance of HEA radiation-resistant materials provides a new idea for nuclear materials, and it has been used as the catalyst in the nuclear energy [97,[101][102][103]. Waseem et al [68] considered that the W x TaTiVCr as low/reduced-activation alloys have a promising future for fusion power plants.…”
Section: Irradiation Propertymentioning
confidence: 99%
“…He et al studied the phase stability and defect cluster formation in CoCrFeNi-based SP-CSAs due to 1250 keV electron irradiation at 400°C up to 1 dpa. 34 It was found that CoCrFeNi exhibits no detectable phase separation/decomposition. By contrast, FeCoCrMnNi and FeCoCrNiPd show L1 0 (NiMn)-type ordering decomposition and h001i-oriented spinodal decomposition between Co/Ni and Pd, respectively (as shown in Fig.…”
Section: Phase Stabilitymentioning
confidence: 99%
“…7), which is similar with the high energy electron irradiation. 34,43 The binary NiFe exhibits the largest loop size and lowest loop density, while NiCoFeCrMn presents the smallest loop size and lowest loop density. However, the ternary NiCoFe and quaternary NiCoFeCr exhibit comparable loop density and loop size.…”
Section: Irradiation-induced Defects and Segregation/ Precipitationmentioning
confidence: 99%